2020
DOI: 10.1007/s12325-020-01382-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Hypothyroidism in Gulf Cooperation Council (GCC) Countries

Abstract: Hypothyroidism is one of the most common chronic endocrine conditions. However, as symptoms of hypothyroidism are non-specific, up to 60% of those with thyroid dysfunction are unaware of their condition. Left untreated, hypothyroidism may contribute to other chronic health conditions. In the Arabian Gulf States, hypothyroidism is thought to be common, but is underdiagnosed, and management approaches vary. An advisory board of leading Saudi endocrinologists and policy advisers was convened to discuss and formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
0
24
0
4
Order By: Relevance
“…[3][4][5] Yet, according to Alzahrani et al, "Hypothyroidism is a common but under-recognized and under-diagnosed condition in the Persian Gulf countries. " 26 Al Shahrani conducted a systemic review in the Middle East region to highlight and consolidate the prevailing data on thyroid disease. They aimed to "present the aggregated burden, risk factors and prognosis of various thyroid diseases prevalent in Arab countries".…”
Section: Thyroid Relation With Ironmentioning
confidence: 99%
“…[3][4][5] Yet, according to Alzahrani et al, "Hypothyroidism is a common but under-recognized and under-diagnosed condition in the Persian Gulf countries. " 26 Al Shahrani conducted a systemic review in the Middle East region to highlight and consolidate the prevailing data on thyroid disease. They aimed to "present the aggregated burden, risk factors and prognosis of various thyroid diseases prevalent in Arab countries".…”
Section: Thyroid Relation With Ironmentioning
confidence: 99%
“…The hypothyroidism patients must be supplied with enough thyroid hormones during the lockdown period and the dose of levothyroxine can be increased (30–50%) in pregnancy cases and regularly monitored assessing the TSH and other clinical parameters to restrain the progression of hypothyroidism. 142 Hypothyroidism cases infected with SARS-CoV-2 do not require any unique diagnostic and treatment options except for the continuation of the treatment of pre-existing hypothyroidism during viral infection. Recent reports showed that hypothyroidism patients did not exhibit any heightened risk of SARS-CoV-2 infection.…”
Section: Thyroid Disease Management: Challenges During and Post-covid-19 Scenariomentioning
confidence: 99%
“…As well as, decrease physical performance with various symptoms may increase an inactive life style. However, left hypothyroidism patients without management can contribute to other chronic health, conditions such as dyslipidaemia, hypertension, cognitive impairment, infertility, neuromuscular problems and Myxedema coma (7) . Therefore, the patients with hypothyroidism require a regular physical activity and copy with those problems because the physical inactivity has been identified as the fourth leading risk factor for global mortality.…”
Section: Introductionmentioning
confidence: 99%